Pengaruh Faktor Lingkungan Terhadap Ikan yang Tertangkap di Perairan Pantai Payum Sampai Perairan Pantai Lampu Satu, Kabupaten Merauke - Bonny Lantang (Faculty of Agriculture Musamus University, 2021)
The coastal waters of Payum to coastal waters of Lampu Satu of the coastal areas in Merauke Regency and are used by fishermen as water areas to catch organisms that have high economic value. This study aims to determine the types and effects of physics and chemistry on the presence of fish in the coastal waters of Payum to Lampu Satu. This research was conducted in the coastal waters of Payum to coastal waters of Lampu Satu, Merauke from April to June 2020. Data collection was carried out by measuring the environmental parameters directly, namely temperature, salinity and pH, while the fish catch data was obtained by calculating directly the number of catches each trip. Data analysis using linear regression model to determine the environmental factors that effect to the catch. The results showed that temperature, salinity and pH had an effect and supported the presence of fish in the coastal waters Payum to coastal waters of Lampu Satu.